2011
DOI: 10.1038/modpathol.2010.187
|View full text |Cite
|
Sign up to set email alerts
|

E-cadherin expression in plasmacytoid, signet ring cell and micropapillary variants of urothelial carcinoma: comparison with usual-type high-grade urothelial carcinoma

Abstract: Loss of E-cadherin expression has been linked to the invasive phenotypes of a variety of neoplasms, including lobular breast cancer. The expression of E-cadherin in variants of urothelial carcinoma relative to usual-type urothelial carcinoma, maximum depth of invasion and angiolymphatic invasion has not been well characterized. A total of eight cases of micropapillary urothelial carcinoma, four cases of plasmacytoid urothelial carcinoma, two cases of urothelial carcinoma with signet ring cell differentiation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
20
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 55 publications
6
20
0
1
Order By: Relevance
“…In our study, we observed re-expression of E-cadherin that was more expressed in pT3 local tumors (69.3%) and that were able to disseminate or recur locally. Interestingly, in agreement with our data, a recent study published by Lim et al (22) found normal expression of E-cadherin in both usual and micropapillary urothelial bladder carcinomas, and that was independent of tumor stage, tumor grade or presence of microvascular invasion. In their study, they proposed that loss of E-cadherin expression may be a characteristic of a histologically special plasmocytoid or signed ring cell urothelial carcinoma.…”
Section: Discussionsupporting
confidence: 82%
“…In our study, we observed re-expression of E-cadherin that was more expressed in pT3 local tumors (69.3%) and that were able to disseminate or recur locally. Interestingly, in agreement with our data, a recent study published by Lim et al (22) found normal expression of E-cadherin in both usual and micropapillary urothelial bladder carcinomas, and that was independent of tumor stage, tumor grade or presence of microvascular invasion. In their study, they proposed that loss of E-cadherin expression may be a characteristic of a histologically special plasmocytoid or signed ring cell urothelial carcinoma.…”
Section: Discussionsupporting
confidence: 82%
“…Only in case of T4 tumors, the expression of all markers showed stable high values. These observations are in agreement with the results of Lim et al (2011). Divergence in the case of E-cadherin expression in T4 tumors can be explained by the fact that in our group we had only one patient in this stage.…”
Section: Disscussionsupporting
confidence: 82%
“…Positivity for epithelial markers, including cytokeratins and epithelial membrane antigen, confirms the epithelial nature of plasmacytoid UC [6, 7, 9]. It has recently been reported that the majority of plasmacytoid UCs show negative or markedly reduced membranous staining for E-cadherin, which mediates cell-to-cell adhesion, suggesting that the loss of E-cadherin expression may be a prominent feature of plasmacytoid UC [9, 10]. In the present case, only the plasmacytoid UC component was negative for membranous E-cadherin, whereas the other histological components were positive for membranous E-cadherin, which is consistent with previous reports [9, 10].…”
Section: Discussionmentioning
confidence: 97%
“…Several previous studies have examined the immunohistochemical features of plasmacytoid UC [6, 7, 9, 10]. CD138 is typically positive in plasmacytoid UC, as is the case in many other carcinomas as well as plasma cell neoplasia [7, 9].…”
Section: Discussionmentioning
confidence: 99%